e_LIPID: Characterisation of the Lipid Profile in the Portuguese Population - Mariano, Cibelle (2016)
AIM: Cardiovascular disease (CVD), particularly coronary heart disease and stroke, are the leading cause of morbidity and mortality worldwide. The common forms of CVD have a complex etiology in which interactions between multiple genetic and environmental factors play an important role. Dyslipidaemia is one of many independent cardiovascular risk factors that have been identified for CVD, and its correct identification is of great importance in order to implement specific interventions, especially for CVD prevention. The aim of this study was the construction of population specific lipid percentiles and the to present the characterization of the dyslipidaemia in the Portuguese population.